Integrating bel canto singing techniques in performing selected Chinese Art Song based on its classical poetry - Liu, Lijia (Tanjong Malim, 2024)
Integrating bel canto singing techniques in performing selected Chinese Art Song based on its classical poetry by Liu, Lijia